A novel light field imaging based 3D geometry measurement technique for turbomachinery blades - Ding, Junfei (2021)
This paper presents a novel snapshot three-dimensional (3D) imaging technique for fast turbomachinery blade geometrical measurements. The proposed measurement system employs a microlens array based light-field camera to capture 3D blade geometry into one light-field image, from which 100 new perspective images can be generated and the blade 3D point cloud can be recovered through sophisticated light-field rendering algorithms. The measurement accuracy is determined to be approximately 35 μm by measuring a series of standard gauge blocks. Performance of the proposed technique is compared against a coordinate-measuring machine (CMM) and laser scanner by measuring a turbine blade. It reveals that the single light-field camera 3D measurement system can produce 820 000 data point in 30 s with an average measurement accuracy of 61.00 μm, which is considerably more efficient than the current CMM and laser scanning techniques.